Experimental evaluation of received signal using blind channel estimation for RFID system via MIMO antenna - Promkeeree, Theerapat; Duangsuwan, Sarun; Promwong, Sathaporn (My University, 2014)
In this paper, we investigate an evaluation of the received signal by using blind channel estimation for radio frequency identification (RFID) system via multiple input multiple output (MIMO) antenna. This method is based on higher order statistic of the received signal to estimate the ambiguity of MIMO antenna. The advantage of blind channel estimation is shown that to achieve the severe of multipath interference, when employed the zero-forcing (ZF) and the minimum mean square error (MMSE) at the receiver. The measurement result is illustrated that the signal verified and estimated of the received signal have been compared. This technique is a novel of signal processing on designing of RFID reader based on MIMO antenna will be utilized. © 2014 IEEE.
Keywords: blind channel estimation; MIMO antenna; RFID system